Interpretation of Gibbs surface excess model for gas adsorption on heterogeneous coal particle. (15th February 2018) - Cao, Liu; Zhang, Yugui
Abstract: Sorption kinetics measurement is the essential prerequisite of constructing adsorption isotherms in the research field of coalbed methane production and CO2 injection, however, Difficulty arises from the fact that sorption kinetics measurement is found to be accompanied by thermodynamic effect (e.g. fluctuation of temperature and pressure); that is, it has a strong dependence on the accuracy of models and methods of adsorption isotherm. In this regard, a new model analogous to Gibbs surface excess (GSE) adsorption is presented in this study for gas adsorption on heterogeneous coal particle in the interest of interpretation and application the GSE theory to the sorption kinetics measurement. According to this model, alternative method of adsorption isotherm calculation is developed in this paper, which suggests that thermodynamic parameters of adsorption measurement are detected in a contrasting and synchronous manner and thus enable the validity of adsorption data to be judged more accurately. Furthermore, feasibility tests were performed and results showed that the current model and method of adsorption isotherm determination could be used to improve experimental accuracy for the integral and incremental sorption step measurements.